Knowing HIV/AIDS epidemic through billboards: awareness campaigns in Viet Nam - de Loenzien, Myriam de (communication orale, 2013)
What do billboards tell us about the HIV / AIDS epidemic and related society? In Viet Nam HIV/AIDS control and prevention policy has been characterized by a strong involvement of the government and drastic changes. Until 2003, the epidemic was considered and presented by the public institutions as a “social evil”. Consequently, its links with drug consumption and commercial sex were emphasized. This resulted in billboards increasing fear and provoking collective disapproval towards people living with HIV/AIDS. This orientation has been abandoned in 2004. From this date on, it has been considered harmful since it would strengthen stigmatization and discrimination attitudes and behaviors towards people living with HIV/AIDS and their relatives. These changes are perceptible in HIV/AIDS awareness campaigns. To illustrate them and show the subsequent contrasts, I use a selection of 37 photographs of billboards taken in and around several cities in the country from 2003 to 2008 when the AIDS law and harm reduction programs had been implemented. They emphasize the transition from a dichotomous vision to a more participative and empathetic approach. They also allow us to visualize the suggested bridging between drug consumption and HIV/AIDS as well as the strength of the norms of solidarity to which everyone, especially families, have to comply. This paper draws lessons and raises questions about the way analysis of HIV/AIDS billboards can provide insights into social life.
Keywords: ⛔ No DOI found